IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS SISWA KELAS IVD SDN 163 PEKANBARU - Tria Yulita Yulita; Hendri Marhadi Marhadi; Otang Kurnia Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background of this study is the low outcomes of social science (IPS) of the fourth grade students of IV D class of SDN 163 Pekanbaru., with the average score of the class is 69,57. Based on the standard minimum criteria (KKM) 70 which has been determined by the school, there were 20 students are below the standard minimum criteria or 57,15% and 15 students are above the minimum standard criteria or 42,85% from overall number of 35 students. This research is an action research which aims to enhance social science (IPS) learning process so that the learning outcomes of the fourth grade students of IVD class of SDN 163 Pekanbaru’ will increase with the implementation of problem-based learning model. Formulation of the problem: How the implementation of problem-based learning model (PBM) in improving IPS learning process?, does the problem-based learning model (PBM) can improve social science learning outcome of fourth grade students of IVD class of SDN 163 Pekanbaru?. This research was carried out on 27 April 2015 until 07 May 2015 with II cycles. The subject of this research is the fourth grade students of IVD class of SDN 163 Pekanbaru with total number 35 students who were became the participants of this research. Data collection instruments in this research are teacher and students activity sheets as well as a written test sheet. The results of this research can be seen from the results of the study before the implementation of problem-based learning mode are given which the average score is 69, 57, after the action is given or after the implementation of problem-based learning model are increased in cycle I, with an average score 73,85 which are increased as much as 6,15%, and in cycle II the average score are increased by 82,28 which are increased as much as 18,28%. It can be concluded that the problem-based learning model can improve social science (IPS) learning process with the increasing of the learning outcomes of fourth grade students of IVD class of SDN 163 in learning social science (IPS). Keywords: problem-based learning Model, the learning process IPS, IPS Study Results